A DESCRIPTIVE STUDY OF THE TEACHERâS TECHNIQUE ON CONTROLLING THE STUDENTSâ MISBEHAVIOR IN SMPN 1 SUKASADA - Pita, Yul Fulgensia Rusman (International Journal of Language and Literature, 2017)
This research aimed at analyzing the English teacherâs technique on controlling studentsâ misbehavior in the classroom. The focus of this research is related with the most frequent misbehavior conducted by the students of class VII G and VII H in SMPN 1 Sukasada, the English teacher technique on controlling studentsâ misbehavior, and the studentsâ responses toward English teacherâs technique during teaching and learning process. This research applied descriptive qualitative study. The writer analyzed the English teacher technique on controlling studentsâ misbehavior in the classroom through observation, video recording, note taking, and interview guidance. The result of the study showed that the most frequent misbehavior conducted by the students were disruption and needless talk. The English teacher at SMPN 1 Sukasada used reprimands and pre-empting misbehavior and the studentsâ responses was good enough. In the last meeting, the students reduce their misbehaviours.Â